The effect of animal-assisted intervention on undergraduate students’ perception of momentary stress - Chute, Andrea; Vihos, Jill; Johnston, Sharon; Buro, Karen; Velupillai, Nirudika (Frontiers in Psychology, 2023)
Background Student mental wellness is a priority in higher education. Animal Assisted Interventions (AAIs’) are gaining momentum in universities across North America (Dell et al., 2015). Aims This study explored the relationships between AAIs’, demographic variables, and perceived momentary stress among university students. Methods Using a descriptive correlational design, students completed a Perceived Momentary Stress questionnaire that included the Stress Numerical Rating Scale-11 (Stress NRS-11) and the Visual Analog Scale (VAS) to measure perceived stress before and after AAIs’. Data were analyzed using R (4.1.2) (R Core Team, Vienna, Austria) to identify relationships between students’ perceptions of momentary stress, AAIs’ and sociodemographic and demographic variables. Results First-year students, female students, and students identifying as sexual minorities were found to benefit the most from AAIs’. Conclusion Results from this study reflect relationships between exposure to animal-assisted interventions and student demographic variables.